Estimativas para os autovalores do operador de Dirac - Araújo, Oslenne Nogueira de (2012)
The aim of this work is to present some estimates for the eigenvalues of the Dirac operator on compact Riemannian Spin manifolds with positive scalar curvature. For this, we use some tools of classical Riemannian geometry and some of its properties as Clifford algebra, spin groups, connections, covariant derivative and Dirac operator.